2019
DOI: 10.1002/ece3.5188
|View full text |Cite
|
Sign up to set email alerts
|

Invasive species removal increases species and phylogenetic diversity of wetland plant communities

Abstract: Plant invasions result in biodiversity losses and altered ecological functions, though quantifying loss of multiple ecosystem functions presents a research challenge. Plant phylogenetic diversity correlates with a range of ecosystem functions and can be used as a proxy for ecosystem multifunctionality. Laurentian Great Lakes coastal wetlands are ideal systems for testing invasive species management effects because they support diverse biological communities, provide numerous ecosystem services, and are increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…increase establishment of habitat-forming perennial speciessuch as completely breaking seed dormancy and improving germination and establishment conditions -may be as conducive to supporting biotic resistance as introducing fast growing annuals (Iannone and Galatowitsch, 2008;Lishawa et al, 2019;Rosbakh et al, 2019).…”
Section: Choosing Native Plants For Functional Goals Including Invasimentioning
confidence: 99%
See 1 more Smart Citation
“…increase establishment of habitat-forming perennial speciessuch as completely breaking seed dormancy and improving germination and establishment conditions -may be as conducive to supporting biotic resistance as introducing fast growing annuals (Iannone and Galatowitsch, 2008;Lishawa et al, 2019;Rosbakh et al, 2019).…”
Section: Choosing Native Plants For Functional Goals Including Invasimentioning
confidence: 99%
“…Alteration of salinity at the site can be addressed with hydrologic flooding, strategic seed sowing timing (section "Optimal Germination Safe Sites and Season"), and selection of species that are able to tolerate higher salinities while providing valuable ecosystem functions (Howard, 2010). Physical suppression and shading of native species should be addressed by removing undesirable vegetation and litter from the site prior to seeding (Lishawa et al, 2019).…”
Section: Unwanted Legacy Effects From Invasive Speciesmentioning
confidence: 99%
“…Evidence has been found that bamboo invasion reduced mean tree height (11.7 m) compared with native broadleaved forest (13.1 m) [29]. Contrarily, certain invasive vegetation removal can increase basal diameter, tree height, and phylogenetic diversity of wetland plant communities [52]. Our Spearman correlation analysis showed that tree height and crown width of A. spinulosa were negatively correlated with two denitrifying bacteria, Chitinophaga and Sorangium, respectively.…”
Section: Relationships Of Denitrifying Bacteria With Soil Properties ...mentioning
confidence: 52%
“…For instance, Lawrence et al (2016) suggested that combined treatment of biomass harvest and disking can add to cattail control and could be a positive economical perspective for farmers due to cattail biomass utilization as biofuel, while at the same time the native plant community will be boosted. Lishawa et al (2019) suggested that restoration techniques of cattail dominant areas should focus on periodic treatments including biomass removal, in order to preserve the native biodiversity. Vroom et al (2018) proposed that T. latifolia can be utilized for the restoration of peatlands after their rewetting, because of the species capacity to control nitrogen and phosphorus concentrations from surface and pore water, as well as regulate CH 4 and N 2 O emissions.…”
Section: Resultsmentioning
confidence: 99%